PENGEMBANGAN PENULISAN CERPEN BERBASIS CERITA RAKYAT (Development of Creating Short Story Based on Folktale) - La Ode ode Syukur; Irianto Ibrahim; La Ode Sahidin; Nur Israfyan Sofyan; NFN Alias (Kantor Bahasa Provinsi Sulawesi Tenggara, 2022)
The process of creating literary works is a creative process that requires a comprehensive imagination space. Literature and human life are two inseparable sides. The existence of short stories has not been widely used as a medium and source of short story writing. Therefore, this study examines the development of short story writing based on folklore. The purpose of this study was to describe and explain the development of writing literary works based on folklore for students of the Department of Indonesian Language and Literature Education, Faculty of Teacher Training and Education, Halu Oleo University. This research uses analytical descriptive method. The data source is in the form of short stories written by students of the Department of Indonesian Language and Literature Education. The results of this study indicate that the development of short story writing based on folklore is carried out through: (1) developing a theme as a short story identity in the form of the emergence of various themes such as brotherhood, affection, patriotism, spirit of life, and work ethic, and honesty, (2) Plot As Storytelling innovation is described by the variety of plots shown for a folklore such as backwards or mixed plots, as well as fleshback plots, and (3) Setting as the field of events Short stories are presented according to the reality of current conditions and atmosphere. Proses penciptaan karya sastra merupakan proses kreatif yang membutuhkan ruang imajinasi komperhensif. Karya sastra dan kehidupan manusia merupakan dua sisi yang tidak dapat terpisahkan. Keberadaan cerita pendek belum banyak digunakan sebagai media dan sumber penulisan cerpen. Oleh karena itu, dalam penelitian ini mengkaji tentang pengembangan penulisan cerpen berbasis cerita rakyat.Tujuan penelitian ini adalah untuk mendeskripsikan dan menjelaskan pengembangan penulisan karya sastra berbasis cerita rakyat pada mahasiswa Jurusan Pendidikan Bahasa Dan Sastra Indonesia Fakultas Keguruan Dan Ilmu Pendidikan Universitas Halu Oleo. Penelitian ini menggunakan metodedeskriptif analitik. Sumber data berupa naskahcerpen yang tulis mahasiswa Jurusan Pendidikan Bahasa Dan Sastra Indonesia. Adapun hasil penelitian ini menunjukkan bahwa pengembangan penulisan cerpen berbasis cerita rakyat dilakukan melalui: (1) pengembangan tema sebagai identitas cerpen berupa munculnya beragam seperti tema persaudaraan, kasih sayang, patriotisme, semangat hidup, dan etos kerja,dan kejujuran, (2) Alur Sebagai Inovasi Penceritaan digambarkan dengan ada variasi alur yang ditampilkan untuk sebuah cerita rakyat seperti dengan alur mundur ataupun alur campuran, maupun alur fleshback, dan (3) Latar sebagai Medan peristiwa Cerpen disajikan sesuai realita kondisi dan suasana masa kini.